MIP does not save the impairment argument against abortion: a reply to Blackshaw and Hendricks. Issue 7 (2nd September 2020) - Crummett, Dustin
Abstract : Perry Hendricks' original 'impairment argument' against abortion relied on 'the impairment principle' (TIP): 'if it is immoral to impair an organism O to the nth degree, then, ceteris paribus, it is immoral to impair O to the n+1 degree.' Since death is a bigger impairment than fetal alcohol syndrome (FAS), Hendricks reasons that, by TIP, if causing FAS is immoral, then, ceteris paribus, abortion is immoral. Several authors have argued that this conclusion is uninteresting, since the ceteris paribus clause is not satisfied in actual cases of abortion: women have reasons for wanting abortions which do not apply to drinking during pregnancy, so all else is not equal, and the conclusion is irrelevant to the morality of actual abortions. In a recent article in this journal, Hendricks and Bruce Blackshaw try to evade this criticism by replacing TIP with the 'modified impairment principle' (MIP): 'if it is immoral to impair an organism O to the nth degree for reason R, then, provided R continues to hold (or is present), it is immoral to impair O to the n+1 degree.' MIP allows us to derive the ultima facie wrongness of abortion (not just its ceteris paribus wrongness) because MIP lacks a ceteris paribus clause. But I argue that this lack also renders MIP false: MIP faces counterexamples and implausibly produces genuine moral dilemmas. Since the moral principle on which it relies is false, the modified impairment argument fails. I close by considering what a principle would need to do for the impairment argument to succeed.